2020
DOI: 10.1007/s40744-020-00203-w
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Disease-Modifying Antirheumatic Drug Prescription Patterns for Rheumatoid Arthritis Among United States Physicians

Abstract: Introduction: Some patients with rheumatoid arthritis (RA) using tumor necrosis factor inhibitors (TNFi) experience inefficacy or lack of tolerability and hence switch to another TNFi (cycling) or to a therapy with another mode of action (switching). This study examined patient characteristics, prescribing patterns and treatment practice for RA in the United States. Methods: Data were from the Adelphi Disease Specific Programme (Q2-Q3 2016). Rheumatologists completed a survey and patient record forms for adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…1 When the initial bDMARD is ineffective, providers decide whether to change to a medication with the same mechanism of action (MoA), known as "cycling," or to a different MoA, known as "switching." Recent data found that cycling is more common than switching, 12 but switchers are more likely to persist on the second therapy than cyclers. 13 Changes in therapy can be challenging to navigate as many insurers require extensive prior authorization and step-therapy requirements and financial assistance is often needed for patients to afford their medication.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 When the initial bDMARD is ineffective, providers decide whether to change to a medication with the same mechanism of action (MoA), known as "cycling," or to a different MoA, known as "switching." Recent data found that cycling is more common than switching, 12 but switchers are more likely to persist on the second therapy than cyclers. 13 Changes in therapy can be challenging to navigate as many insurers require extensive prior authorization and step-therapy requirements and financial assistance is often needed for patients to afford their medication.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In one study of 631 patients, the first line therapy was TNF inhibitors for 535 (84.4%) of patients, and 163 (25.8%) changed to second use targeted therapy during the study period: 60.7% to another TNF inhibitor, 39.3% to a different MoA. 12 We found lower rates of switching and cycling in our sample: 84% of the sample did not switch or cycle during the twelve-month period, 9% of patients switched, 5% cycled, and 2% both switched and cycled. At the outpatient rheumatology switched or cycled were 35% less likely to have higher adherence than those without a switch or cycle (OR = 0.65, 95% CI: 0.47 to 0.91, P = 0.011).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…janus kinase (JAK) inhibitors], can control disease activity and thus prevent joint destruction. 6 9 Moreover, in the last 20 years, RA has become milder, with patients exhibiting fewer severe extra-articular manifestations and lower mortality rates. 10 , 11 However, patients with RA still exhibit excess mortality, especially from cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…when a treatment target is not met) [4][5][6]. Of the five currently available anti-TNFs, infliximab, etanercept and adalimumab are the most commonly prescribed, collectively accounting for around 90% of anti-TNF prescriptions for RA [7][8][9][10]. Reference product adalimumab (Humira; AbbVie Inc., North Chicago, IL), reference product infliximab (Remicade; Janssen Biotech, Horsham, PA) and reference product etanercept (Enbrel; Immunex Corporation, Thousand Oaks, CA) are approved by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for indications including RA [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have demonstrated comparable efficacy between infliximab, etanercept, adalimumab, certolizumab and golimumab[66,67]; however, golimumab and certolizumab were not considered in the present review as they account for less than 10% of anti-TNFs prescribed for RA[9,10]. Aaltonen and colleagues conducted a systematic literature review and analysis of 26 RCTs and concluded that no single agent clearly rose above the others in terms of efficacy[67].…”
mentioning
confidence: 99%